Peranan jururawat dan kepuasan hati keluarga terhadap perancangan discaj untuk pesakit yang mengalami kecederaan kepala di Hospital Universiti Sains Malaysia (HUSM) - Hamidah, Abd Majid (Universiti Sains Malaysia, 2008)
Head injury is a one of the causes of high mortality rate in United States (US) (Hargrove-Huttle, 2005). According to The National Head Injury Foundation, head injury is a traumatic injury affect changing in physical, mental, emotion, social and vocational (Lemone & Burke, 2004). Patient with head injury also have disturbance in level of conciousness, injury at face area, lung, heart, spinal, abdomen and other side of the body. So, discharge planning is important for their family because patient needs caring from caregivers. This research aimed to determine discharge planning among caregivers. This research also to examine the nurses role in giving discharge planning for family with head injury patiens, to identify levels of satisfaction of family and to determine the obstacle in applying the discharge planning among the nurses for family with head injury patients. This study was a quantitative research based on correlatif descriptif to determine the nurses role and family satisfaction with discharge planning at surgical ward in HUSM. A crosssectional study was conducted. The instrwnent of this study consisted of questionnaire. Of the 60 nurses and 60 caregivers enrolled in this study, and the result shows that the levels of nurses role in discharge planning at a everage level. Result in levels of family satisfaction also at a everage level. Based on result of this study, obstacle occur during applying the discharge planning. To identify the relationships between nurses role and family satisfaction, pearson correlation was use and the result shows r = 1.0. To detennine the relationships between nurses role and the obstacle during applied discharge planning, pearson correlation was use and the result shows r = .320. This study found that nurses role was important in discharge planning to encourage caregivers to care more for head injury patients especially to increase the quality of nursing care by decreasing lenght of hospitalization and decrease readmission. And also to maked caregivers involment in caring for head injury patients during hospitalization in relation to identifying caregivers' understanding about caring responsibility, their competencies and confidence in providing care for head injury patients after discharge. If the care of patients were done in the right way, care of patients will be maintained and the risk of complication will reduced.